Long-term Effects of Skin Tearing on Outcomes After Collagenase Treatment of Dupuytren Contractures. (November 2021) - Zhang, Dafang; Blazar, Philip; Benavent, Kyra A.; Earp, Brandon E.
Background: The objective of this study was to compare the rates of recurrence, additional treatment, patient satisfaction, and willingness to undergo Clostridium histolyticum (CCH) treatment again for Dupuytren disease in patients with and without skin tearing at minimum 5-year follow-up.Methods: We identified 199 digits in 142 patients who underwent CCH treatments for Dupuytren disease from April 2010 to December 2013 with minimum 5-year follow-up. Patients were contacted by telephone to collect our response variables: perceived recurrence of contracture, additional treatment, satisfaction, and willingness to undergo CCH treatment again. Medical records were reviewed for skin tearing at manipulation and patient-related and disease-specific variables.Results: At the time of manipulation, 16 out of 142 patients (11%) and 22 out of 199 digits (11%) had skin tearing. Older age was associated with skin tearing. At an average 7.2-year follow-up, the mean satisfaction was 7.1 ± 2.6 on a 1 to 10 Likert scale for patients with skin tearing and 6.5 ± 3.4 for patients without skin tearing. Eighty-one percent of patients with skin tearing expressed willingness to undergo CCH treatment again, compared with 68% of patients without skin tearing. Perceived recurrence of contracture occurred in 82% of digits with skin tearing and 80% of digits without skin tearing. Additional treatment was performed in 45% of digits with skin tearing and 54% of digits without skin tearing. No difference was statistically significant.Conclusions: Although skin tearing at CCH manipulation complicates the short-term course following CCH treatment, it does not affect long-term perceived contracture recurrence or patient satisfaction.